Three Parts Of Counterfeiting: Pirate Production, Grey Import And Imitations - Светлана Юрьевна Барсукова (Journal of Economic Sociology, 2010)
The paper shows that counterfeiting includes substantively different elements: pirate products, grey import and imitations, which rely on different logics of economic reasonability and social legitimization. These summands infringe upon consumers’ interests to a certain degree what makes them selective ally of authorities in the fight with counterfeiting. The author describes the specifics of these three main parts of counterfeiting business from the participants’ structure point of view as well as stimulus and restrictions of their business activity.